Religion and mental health - Schumaker, John F., 1949- (Oxford University Press, 1992)
This is an interdisciplinary collection of previously unpublished papers on the much-disputed relationship between religious behavior and mental health. Schumaker has assembled a distinguished international roster of contributors - sociologists and anthropologists as well as psychiatrists and psychologists of religion. Taken together, the papers provide a comprehensive overview of the current state of research in the field, as well as shedding new light on a number of specific topics, subject groups, and interpretive perspectives.